DCC functions as an accelerator of thalamocortical axonal growth downstream of spontaneous thalamic activity - Castillo-Paterna, Mar (EMBO Rep, 2015)
Controlling the axon growth rate is fundamental when establishing brain connections. Using the thalamocortical system as a model, we previously showed that spontaneous calcium activity influences the growth rate of thalamocortical axons by regulating the transcription of Robo1 through an NF-κB-binding site in its promoter. Robo1 acts as a brake on the growth of thalamocortical axons in vivo. Here, we have identified the Netrin-1 receptor DCC as an accelerator for thalamic axon growth. Dcc transcription is regulated by spontaneous calcium activity in thalamocortical neurons and activating DCC signaling restores normal axon growth in electrically silenced neurons. Moreover, we identified an AP-1-binding site in the Dcc promoter that is crucial for the activity-dependent regulation of this gene. In summary, we have identified the Dcc gene as a novel downstream target of spontaneous calcium activity involved in axon growth. Together with our previous data, we demonstrate a mechanism to control axon growth that relies on the activity-dependent regulation of two functionally opposed receptors, Robo1 and DCC. These two proteins establish a tight and efficient means to regulate activity-guided axon growth in order to correctly establish neuronal connections during development.